1993
DOI: 10.1002/ar.1092370408
|View full text |Cite
|
Sign up to set email alerts
|

Isolated pancreatic islets of the rat: An immunohistochemical and morphometric study

Abstract: Although there is a recent increase in the use of the isolated pancreatic islets of the rat in the transplantation and functional studies, there has been no detailed quantitative assessment on the size and cellular constituents of islets after the isolation procedure. The present work was undertaken to study the size classes of the isolated islets and the morphometry of their cellular populations. Islets of the rat pancreas were isolated by using the intraductal collagenase digestion technique, the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…1980; Schwartz & Traverso, 1984). Furthermore, it has been demonstrated in isolated islets that a decrease in ATP concentration and ATP/AMP ratio was related to the time of incubation within the isolation procedure (El‐Naggar et al. 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1980; Schwartz & Traverso, 1984). Furthermore, it has been demonstrated in isolated islets that a decrease in ATP concentration and ATP/AMP ratio was related to the time of incubation within the isolation procedure (El‐Naggar et al. 1993).…”
Section: Discussionmentioning
confidence: 99%
“…1990), but relatively few studies have focused on morphological investigations (Tahir et al. 1992; El‐Naggar et al. 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Islets were picked by hand and cultured in CMRL-1066 (Gibco, Rockville, MD) containing 5.5 or 16.6 mmol/l glucose, 10% (vol/vol) fetal calf serum (Hyclone Laboratories, Logan, UT), 2 mmol/l L-glutamine, 100 U/ml penicillin, and 100 mg/l streptomycin (Sigma) (18) at 37°C in humidified air containing 5% CO 2 . The islet isolation procedure yielded islets in which most peripheral cells were ␤-cells, as previously described by El-Naggar et al (19). h-IAPP added to islets in culture under these conditions will therefore encounter predominantly ␤-cells.…”
Section: Mouse Islet Cell Toxicity Experimentsmentioning
confidence: 99%
“…Although functional studies of the cultured islets were reported by many authors (Slavin et al, 1977;Dudek et al, 1980;Georgiou and Mandel, 1984;Mourmeaux et al, 1985;Yang and Wu, 1989;Leduque et al, 1992;El-Naggar et al, 1993), we could not find, however, any comprehensive study combining the effect of cryopreservation/post-thaw culture with the morphological findings. Although a few authors (Dawidson et al, 1988;Von Mach et al, 2003) described some structural aspects of the cultured cryopreserved fetal islets, however, detailed comprehensive correlation of structure and function was not documented.…”
Section: Discussionmentioning
confidence: 61%